Analisis Tingkat Kepuasan Pelanggan Terhadap Pengguna Jasa Layanan Grab Menggunakan Metode C4.5 - Permatasari, Veren Nita; Aula, Raisah Fajri; Akbar, Yuma; Hidayat, Aditya Zakaria (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Technological advances have brought significant changes in various aspects of life, including transportation. Grab as one of the pioneers of online transportation services in Indonesia is the main choice for many people. However, competition among online transportation service companies forces each service provider to compete in improving the quality of their services. This study aims to analyze the level of customer satisfaction with the use of Grab services using the C4.5 method. This method was chosen because of its ability to form a decision tree model that helps identify the main factors that influence customer satisfaction. The data for this study were obtained from a survey of Grab customers who used Grab driver services within a certain period of time. The survey covered various aspects of user experience, such as Ease of Use of the Application, Service Availability, Waiting Time, Price, Security. The data was analyzed using the C4.5 algorithm to gain an in-depth understanding of the factors that influence the level of customer satisfaction. The analysis shows that the C4.5 method is effective in identifying factors that influence customer satisfaction. The results of the rapidminer test show the accuracy of the C4.5 algorithm from 100 respondent data obtained, which is 94.00%. These results are expected to provide valuable input for the Grab company and drivers in an effort to improve the quality of their services.